The THO complex coordinates transcripts for synapse development and dopamine neuron survival - Maeder, Celine I. (Cell, 2018)
Synaptic vesicle and active zone proteins are required for synaptogenesis. The molecular mechanisms for coordinated synthesis of these proteins are not understood. Using forward genetic screens, we identified the conserved THO nuclear export Complex (THOC) as an important regulator of presynapse development in C. elegans dopaminergic neurons. In THOC mutants, synaptic messenger RNAs are retained in the nucleus, resulting in dramatic decrease of synaptic protein expression, near complete loss of synapses and compromised dopamine function. CRE binding protein (CREB) interacts with THOC to mark synaptic transcripts for efficient nuclear export. Deletion of Thoc5, a THOC subunit, in mouse dopaminergic neurons causes severe defects in synapse maintenance and subsequent neuronal death in the Substantia Nigra Compacta. These cellular defects lead to abrogated dopamine release, ataxia and animal death. Together, our results argue that nuclear export mechanisms can select specific mRNAs and be a rate-limiting step for neuronal differentiation and survival.